2020
DOI: 10.1038/s41598-020-66210-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern of Bois noir: case study of a delicate balance between disease progression and recovery

Abstract: Bois noir (Bn) is the most important phytoplasma disease of euro-Mediterranean area and induces severe loss of production and even the death of vines. Understanding the delicate balance between disease progression and recovery of Bn infected plants over space and time is crucial to set up management tools. the data collected and analysed allowed to provide insights into dispersal pattern of the disease, caused by'Candidatus phytoplasma solani'. point pattern analysis (ppA) was applied to assess the spatial arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Considering that most symptomatic grapevines were not replaced throughout the years, it follows that many vines previously diseased did not show any symptoms in the following seasons. Such dynamics confirmed the existence of balanced equilibrium between driving forces acting on BN impact (Murolo, Garbarino, Mancini, & Romanazzi, 2020; Rotter et al, 2018). In particular, vector‐mediated CaPsol transmission to grapevines (new infections) and symptom remission were equally strong drivers in Erbusco, while the latter was prevalent in Corte Franca.…”
Section: Discussionsupporting
confidence: 59%
“…Considering that most symptomatic grapevines were not replaced throughout the years, it follows that many vines previously diseased did not show any symptoms in the following seasons. Such dynamics confirmed the existence of balanced equilibrium between driving forces acting on BN impact (Murolo, Garbarino, Mancini, & Romanazzi, 2020; Rotter et al, 2018). In particular, vector‐mediated CaPsol transmission to grapevines (new infections) and symptom remission were equally strong drivers in Erbusco, while the latter was prevalent in Corte Franca.…”
Section: Discussionsupporting
confidence: 59%
“…Firstly, the nearest neighbor distance index (NNI). The calculation result of the average distance between the closet attractions is compared with that between nodes in the random distribution to analyze the degree of deviation from the random distribution, so as to obtain the distribution type of rural tourism attractions [ 34 ]. The calculation can be written as …”
Section: Construction and Evaluation Of Rural Tourism Spatial Pattern Based On Multifactor-weighted Neural Network Algorithmmentioning
confidence: 99%
“…The same grapevines were sampled again in the early growing season of 2020. In 2020, the grapevines did not develop symptoms over the summer, and phytoplasmas were not detected in samples from these grapevines later in the growing season, which suggested that these grapevines had already recovered from their previous infection or were in the recovery process [ 41 ]. Moreover, the RNA-Seq analysis of samples from these grapevines revealed that there was not even a single differentially expressed gene defined between the recovered and uninfected grapevines ( Table S1 ), which indicated that the recovery appeared to have occurred previously, in 2018 or 2019 [ 20 ].…”
Section: Resultsmentioning
confidence: 99%